2020
DOI: 10.30659/e.5.2.192-201
|View full text |Cite
|
Sign up to set email alerts
|

Teaching English allomorphs through �Harry Potter and the Chamber of Secret� movie

Abstract: The study is primarily concerned with the use of �Harry Potter and the Chamber of Secret� to teach English allomorphs in EFL classrooms. This paper is an alternative way to teach them as a significant element of pronunciation. The types examined are�Regular Past Tense, Regular Plural Number, Third Person Present, The Regular Possessive, and�Reduced IS and HAS. Besides the main highlight of allomorph pronunciation, the movie also contemplates some suprasegmental features called word stress and sentence intonati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…The rapid development of computer technology and the wide application of multimedia learning platforms in teaching have realized the integrated presentation of multiple sensory channels such as vision and hearing, so that the teaching classroom can easily exceed the limitations of time and space; compared with traditional teaching, with the support of information technology The modern teaching model is more three-dimensional, diverse and practical [8]. With the widespread popularization of mobile Internet technology, teachers can easily use portable PCs, smart phones, etc.…”
Section: Junior High School English Teaching Methods Under the Micro-...mentioning
confidence: 99%
“…The rapid development of computer technology and the wide application of multimedia learning platforms in teaching have realized the integrated presentation of multiple sensory channels such as vision and hearing, so that the teaching classroom can easily exceed the limitations of time and space; compared with traditional teaching, with the support of information technology The modern teaching model is more three-dimensional, diverse and practical [8]. With the widespread popularization of mobile Internet technology, teachers can easily use portable PCs, smart phones, etc.…”
Section: Junior High School English Teaching Methods Under the Micro-...mentioning
confidence: 99%
“…At the same time, they recognize the class of the words whether they belong to noun, pronoun, adjective, verb, adverb, conjunction, and preposition while watching the video (Sakkir & Usman, 2018;Abdulrahman & Basalama, 2019). In general, studies have confirmed the increase in students' vocabulary mastery by implementing YouTube videos in English (Ali & Jabar, 2016;Aniuranti & Suwartono, 2020;Sakkir & Usman, 2018;Samsi, 2016;Styati, 2016).…”
Section: The Benefits Of Youtube Videos For Improving Students' Englishmentioning
confidence: 97%
“…Movies have been implemented by Abdullah et al (2020), Aniuranti & Suwartono (2020), Damar (2014), Ismaili (2013), Obaidullah & Rahman (2018), Sakkir & Usman (2018), Silviyanti (2014), andStyati (2016) because they are entertaining due to its combination between story, facial expressions, songs, and music. Movie video is a type of video that is often watched on YouTube because of its entertaining nature (https://destaniamovie.blogspot.com).…”
Section: Figure 1 Types Of Youtube Videos Used As Learning Mediamentioning
confidence: 99%
See 1 more Smart Citation
“…In English pronunciation, there are many types of allomorphs that can be found. However, the teacher can choose to provide an explanation of 3-5 allomorphs commonly found in reading texts such as the use of (d/ed) in the regular past tense, (s/es) in the regular plural number, the suffix (s) in the third person present, and ('s) in the regular possessive (Aniuranti et al, 2020). Then the teacher can explain what is meant by an allomorph (see table 1) and provide the example of how to pronounce a morpheme according to the formula for pronouncing consonants (see table 2).…”
Section: Table 2 Place and Manner Of Articulationmentioning
confidence: 99%